If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + 3 = 2(x + -9) Reorder the terms: 3 + -5x = 2(x + -9) Reorder the terms: 3 + -5x = 2(-9 + x) 3 + -5x = (-9 * 2 + x * 2) 3 + -5x = (-18 + 2x) Solving 3 + -5x = -18 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 3 + -5x + -2x = -18 + 2x + -2x Combine like terms: -5x + -2x = -7x 3 + -7x = -18 + 2x + -2x Combine like terms: 2x + -2x = 0 3 + -7x = -18 + 0 3 + -7x = -18 Add '-3' to each side of the equation. 3 + -3 + -7x = -18 + -3 Combine like terms: 3 + -3 = 0 0 + -7x = -18 + -3 -7x = -18 + -3 Combine like terms: -18 + -3 = -21 -7x = -21 Divide each side by '-7'. x = 3 Simplifying x = 3
| -22+19c=15 | | X+50+115=180 | | 2x-3=7x-3 | | j-0.2=0.8 | | 6(5x+5)=300 | | 2(x+4)+5x=64 | | 79-y=2y+22 | | N/2-7=-45 | | 2(x+4)+5x=-32 | | a^2-7ab+10b^2= | | 8+10+4y+2=60 | | 5(X-8/5)=5x+ | | 4x+1+2x=1 | | 8-15=41 | | 12=-6x+8x | | 49u-64= | | 5x-3y-13=0 | | X(x-1)(2x-3)=0 | | B=8/7(j-43) | | z-13+w=180 | | -4a+12a+-2=-18 | | 3/16×3/4 | | sin(pi*x)=0 | | 3x-y+18=0 | | X(3x+2)(3x-2)=0 | | 56/G=7 | | 18n^2+102n-168=0 | | 5x+26=3+8x-7 | | 7+4=2(7+-5) | | 4s-3(s+4)=2(w+5)+4 | | 12/5=3/x | | -3/8-13/8+1=5 |